ASSOCATION DIABETES MELLITUS AND CELIAC DISEASE : A SYSTEMATIC REVIEW - Effendy, Kgs. Mahendra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The incidence of diabetes mellitus, a persistent metabolic condition, has been steadily climbing at an alarming rate all over the world. This condition represents a substantial danger to the wellbeing of people living in all parts of the world. Celiac disease is an immune-mediated condition that affects a person for their entire life. It is characterized by gluten-triggered inflammation and morphological damage of the small bowel mucosa in genetically susceptible individuals. Celiac disease can be prevented by avoiding foods that contain gluten. One of the surprising revelations that came out of this latest investigation was the realization that type 1 diabetes is significantly overrepresented in particular in males who have celiac disease. On the other hand, the prevalence of type 2 diabetes was practically identical to that of the overall Finnish population. People who have celiac disease and also have type 1 or type 2 diabetes are more likely to experience severe comorbidities, and type 1 diabetes is associated with a poorer rate of adherence to a gluten-free diet than celiac disease alone. 16 According to the findings of this study, patients who have type 1 diabetes have an incidence of CeD that is up to twice as high. This is connected to autoimmune disease, which is the pathophysiology of type 1 diabetes as well.